New synonyms, lectotypifications and taxonomical notes on the genus Flemingia (Phaseoleae, Papilionoideae, Leguminosae) from Thai-Indochinese floristic region - Do, Truong Van; Xu, Bo; Gao, Xin-Fen (Phytotaxa, 2018)
We here proposed Flemingia cavaleriei, F. wangkae, and F. sarmentosa, are new synonyms of F. fluminalis, F. kerrii, and F. paniculata, respectively, based on taxonomic literature, type specimens, protologue and recent observation. Additionally, the lectotype of F. cavaleriei and F. sootepensis are designated, and the taxonomical notes and nomenclature of F. fluminalis are also discussed.